2008
DOI: 10.1007/s11010-008-9730-8
|View full text |Cite
|
Sign up to set email alerts
|

Potential problems inherent in cell-based stable NF-κB–GFP reporter systems

Abstract: The nuclear factor-κB (NF-κB) family of transcription factors plays a central role in numerous physiological processes including development, cell survival, immunity and inflammation. We generated a series of stable clonal lines in mouse embryonic fibroblasts carrying NF-κB-GFP plasmid as a reporter. These cell lines were selected by flow cytometry for their high responsiveness to tumor necrosis factor (TNFα) or lipopolysaccharide (LPS), two classic NF-κB inducing stimuli. Although all clones were generated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Our global analysis of mRNA expression also revealed that care should be taken to use GFP-expressing vectors as a control as our results clearly reveal a dominant negative effect on Cxcl2 mRNA but also on ActB and Ube2l3 expression. This is in line with recent studies showing that GFP inhibits IL-2 expression in T cells and that NF-κB-driven GFP reporter constructs deteriorate expression of LPS- or TNF-induced endogenous IL6 and Cxcl1 genes ( 79 , 80 ). This might be due to defective polyubiquitinylation in GFP expressing cells which can perturb ubiquitin-based signaling cascades ( 81 ).…”
Section: Discussionsupporting
confidence: 91%
“…Our global analysis of mRNA expression also revealed that care should be taken to use GFP-expressing vectors as a control as our results clearly reveal a dominant negative effect on Cxcl2 mRNA but also on ActB and Ube2l3 expression. This is in line with recent studies showing that GFP inhibits IL-2 expression in T cells and that NF-κB-driven GFP reporter constructs deteriorate expression of LPS- or TNF-induced endogenous IL6 and Cxcl1 genes ( 79 , 80 ). This might be due to defective polyubiquitinylation in GFP expressing cells which can perturb ubiquitin-based signaling cascades ( 81 ).…”
Section: Discussionsupporting
confidence: 91%
“…As shown previously by El-Guendy and colleagues, NFκB transcriptional activity can be measured by an NFκB reporter gene assay (El-Guendy and Sinai 2008 ). Stably transfected HEK 293 Nano-PEST cells showed an almost 25-fold increase in Nanoluciferase activity after stimulation with 25 ng/ml TNFα for 3 h. This increase could be significantly and dose-dependently decreased by 31.0, 34.7, and 42.1% after 8 h of pre-incubation with EA 575 ® concentrations of 40, 80, and 240 µg/ml, respectively (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Finally, to assess directly NF-κB transcriptional activity, we measured CXCL-1 (GRO-1) and CXCL-2 (GRO-2) mRNAs, broadly accepted as NF-κB target genes ( El-Guendy and Sinai, 2008 ; Patterson et al. , 2013 ).…”
Section: Resultsmentioning
confidence: 99%